Análisis de las debilidades existentes en el sistema de facturación del Comercial Escobar de la Ciudad de Vinces. - Alarcón Monserrate, Ariana Fernanda (2019)
In recent years it can be seen that most companies feel the need to use information systems as a technology framed in commercial activities, in this way computer systems can be adjusted to the needs that the company requires. Computer systems place different functions to obtain better control over the financial movements of a company. In this case of study, it tries to analyze the weaknesses that are framed in the surface of the billing system of Comercial Escobar of the city of Vinces, as well as the income and expenses of merchandise, the lack of products in the warehouse and in turn the expiration of these, as well as the lack of modules that are very necessary for the management of certain important processes in the management of this Commercial. Technological systems are surrounded worldwide, currently the commercial Escobar makes use of technology to improve the processes within the company and thus to obtain a better performance in said Commercial. One of the main problems presented by the commercial Escobar of the City of Vinces, is the lack of modules in the system to streamline processes, such as the inventory process that is not constantly updated, another point is that the user can not see the existence of a product until the expenditures that are normally made on the 25th of each month separately, for that reason we must wait for the inventory to be updated. For the elaboration of this case study, the Field Research Methodology was used since it allows the collection of information through interviews.